ANALISIS PENGKONDISIAN UDARA AC TERHADAP BEBAN PENDINGIN PADA MOBIL DAIHATSU FEROSA - Lufti, Aryananta; Harjanto, Budi; Suparyana (PPM Sdirjianbang Akademi Militer, 2023)
There are components in a vehicle that are supporting components that are important in driving comfort that the air conditioning system components, air conditioning systems is something that appeals to the vehicle due to the kind of machine that works following the thermodynamic cycle. Air-conditioning or airconditioner in passenger cars, usually used to control the temperature of the moisture so the air remains fresh and clean. The main source affecting the cooling load is derived from direct solar radiation and also of the rider or passenger. The purpose of this planning design alone - the eye to provide a basis for estimating the thermal load in the vehicle cabin. From the calculation of the load, the cooling capacity can be calculated so as to enable us to know the size of the cooling load in need. The scope includes design planning of the outdoor heat load that includes loads of heat from sunlight through glass windows as well as loads of heat from sunlight through the walls or roof, while for the heat load of the room includes heat load of the occupants of the room. The amount of cooling load occurs in accordance with the geometric size of the car that is designed for 6 people was 3.66 kW. This burden is still able to be solved by setting the engine coolant, which for the overall heat that can be absorbed by the cabin was 5.26 kW.